Methotrexate analogues display enhanced inhibition of TNF-α production in whole blood from RA patients. (January 2014) - van der Heijden, JW; Assaraf, YG; Gerards, AH; Oerlemans, R; Lems, WF; Scheper, RJ; Dijkmans, BAC; Jansen, G
Abstract : Objectives: Although methotrexate (MTX) is the anchor drug in the treatment of rheumatoid arthritis (RA), patients experience clinical resistance to MTX upon prolonged treatment. We explored whether new-generation antifolates elicit superior anti-inflammatory properties when compared to MTX, based on their capacity to inhibit tumour necrosis factor (TNF)-α production. Method: T cells in whole blood from 18 RA patients (including MTX-naïve, MTX- responsive, and MTX non-responsive patients) and seven healthy volunteers were stimulated with αCD3/αCD28 antibodies and incubated ex vivo for 72 h with MTX and eight novel antifolate drugs with potentially favourable biochemical and pharmacological properties. Drug concentrations exerting 50% inhibition (IC-50) of TNF-α production (by enzyme-linked immunosorbent assay, ELISA) were determined as an estimate for their anti-inflammatory capacity. In addition, induction of T-cell apoptosis was evaluated by flow cytometry. Results: The new-generation antifolates PT523, PT644, raltitrexed, and GW1843 proved to be potent inhibitors of TNF-α production in activated T cells from all three groups of RA patients and from healthy volunteers. Based on IC-50 values, these antifolates were up to 10.3 times more potent than MTX. The anti-inflammatory effects were observed at drug concentrations that provoked suppression of T-cell activation and induction of apoptosis in 20–40% of activated T cells. Conclusion: In an ex-vivo setting, novel antifolates elicited marked inhibition of TNF-α production in activated T cells from RA patients. Further clinical evaluation is warranted to investigate whether a low dosage of these antifolates can elicit immunosuppressive effects equivalent to MTX, and whether they are superior to MTX in patients who fail to respond to MTX.